Taxonomy of Polygonoideae (Polygonaceae): A new tribal classification (2011)
The subfamily Polygonoideae has a world-wide distribution and is an important component of many countries' floras. In this study we present the most comprehensive sampling available to date, including data from three chloroplast genes (matK, ndhF, rbcL) for 82 species in Polygonaceae (54 from Polygonoideae). Based on our results, we propose a new taxonomic classification for Polygonoideae that includes five well-supported tribes: Calligoneae, Fagopyreae, Persicarieae, Polygoneae, and Rumiceae. Overall, the results from molecular data represent significant progress in understanding the evolutionary relationships of major groups within the family. This classification also provides an assessment of diagnostic morphological characters for the tribes. The present work will promote reevaluation of morphological characters within this diverse group, especially synapomorphies for Polygonoideae, and for tribes with a particularly complex history such as Fagopyreae, Persicarieae, and Polygoneae. A new combination, Fagopyrum tibeticum, is proposed.